Field Populations of Wild Apis cerana Honey Bees Exhibit Increased Genetic Diversity Under Pesticide Stress Along an Agricultural Intensification Gradient in Eastern India. Issue 3 (11th May 2018) - Chakrabarti, Priyadarshini; Sarkar, Sagartirtha; Basu, Parthiba
Abstract: Pesticides have been reported to be one of the major drivers in the global pollinator losses. The large-scale decline in honey bees, an important pollinator group, has resulted in comprehensive studies on honey bee colonies. Lack of information on native wild pollinators has paved the way for this study, which highlights the underlying evolutionary changes occurring in the wild honey bee populations exposed to pesticides along an agricultural intensification landscape. The study reports an increased genetic diversity in native Apis cerana Fabricius (Hymenoptera: Apidae) populations continually exposed to pesticide stress. An increased heterozygosity, evidenced by a higher electrophoretic banding pattern, was observed in the pesticide-exposed populations for two isozymes involved with xenobiotic metabolism—esterase and glucose-6-phosphate dehydrogenase. Differential banding patterns also revealed a higher percentage of polymorphic loci, number of polymorphic bands, Nei's genetic distance, etc. observed in these populations in the Randomly Amplified Polymorphic DNA–Polymerase Chain Reaction (RAPD–PCR) experiments using three random decamer primers. Higher heterozygosity, being indicative of a more resistant population, implies population survival within the threshold pesticide stress. This study reports such changes for the first time in native wild Indian honey bee populations exposed to pesticides and has far-reaching implications on the population adaptability under pesticide stress.